TERAPI REALITAS DENGAN MODELING PADA ANAK RENTAN PUTUS SEKOLAH DI YAYASAN USAHA MULIA CIPANAS CIANJUR - Muttaqin, Azka Izdad; Susilowati, Ellya; Rasalwati, Uke Hani (Jurnal Ilmiah Kebijakan dan Pelayanan Pekerjaan Sosial (Biyan), 2024)
Reality therapy with modeling is the result of engineering psychosocial therapy technology by modifying the steps of reality therapy with modeling  aimed at being more effective with the involvement of peer groups and figures who can inspire children. Reality therapy with modelingis used to deal with the problems of children who are vulnerable to dropping out of school with the issue of low learning motivation. This study aims to explain the results of the implementation of WDEPC+M reality therapy technology engineering on increasing the learning motivation of children who are vulnerable to dropping out of school. This study uses a quantitative approach with Single Subject Design (SSD) the type of reversal used is A-B-A. the subjects in this study were GW, NA, and SW. The target behavior observed in this study was related to learning motivation, namely being lazy to go to school, easily giving up on learning, being lazy to do assignments or homework. The validity test of the measuring instrument used percent agreement. Then the data analysis used in this study is a visual analysis consisting of analysis in conditions and between conditions. The results of the study indicate that reality therapy with modeling has an effect on increasing the learning motivation of research subjects, namely children who are vulnerable to dropping out of school, which can be seen through the analysis of data trends with increasing trends and the percentage of overlapping data in the analysis between conditions is below 90% because the smaller the percentage of overlapping data, the stronger the influence of the intervention on changes in the behavior of research subjects.